2002
DOI: 10.1002/app.10756
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphology of ternary‐phase polypropylene/glass bead/ethylene‐propylene rubber composites on the toughness and brittle‐ductile transition

Abstract: ABSTRACT:Correlation between the morphology and the impact toughness was studied for ternary-phase polypropylene (PP)/glass bead (GB)/ethylene-propylene rubber (EPR) composites containing 5-40 vol % of rigid filler at a fixed volume fraction ratio EPR/GB equal to 0.33. The three following types of phase morphology were obtained: (1) separate dispersion of phases and weak GB-PP adhesion; (2) separate dispersion of phases and high GB-PP adhesion; and (3) encapsulation of GB particles by elastomer shell. Maleated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…Before the determination of modulus specimens were allowed to relax for 15 min, during which the interfacial bond could have reformed completely. Several authors, including Vollenberg et al [17] and Dubnikova et al [31] claim that initiation occurs in the increasing part of the stress vs. strain curve (see Figure 1), while Pukánszky et al [6] found that initiation occurs at the maximum of the curve, i. e. at yielding. Although this question cannot be decided here, we may assume that modulus starts to decrease when the specimen was subjected to sufficient prestrain resulting in limited plastic deformation, which prevents the reformation of the original interfacial bonds.…”
Section: Extent Of Debondingmentioning
confidence: 99%
“…Before the determination of modulus specimens were allowed to relax for 15 min, during which the interfacial bond could have reformed completely. Several authors, including Vollenberg et al [17] and Dubnikova et al [31] claim that initiation occurs in the increasing part of the stress vs. strain curve (see Figure 1), while Pukánszky et al [6] found that initiation occurs at the maximum of the curve, i. e. at yielding. Although this question cannot be decided here, we may assume that modulus starts to decrease when the specimen was subjected to sufficient prestrain resulting in limited plastic deformation, which prevents the reformation of the original interfacial bonds.…”
Section: Extent Of Debondingmentioning
confidence: 99%
“…A large variety of materials used, or at least experimented as fillers in composites. Besides CaCO 3 and carbon black (see Table 1) a large number of other materials like mica [44,62], short [63,64] and long glass fibers [65,66], glass beads [67][68][69][70][71][72], sepiolite [24][25][26][27][28], magnesium and aluminum hydroxide [73][74][75], wood flour and cellulose [19][20][21][22][23][76][77][78], wollastonite [79,80], gypsum [81,82], clay [62], metal powders (aluminum, iron, nickel) [83,84], steel fibers [85], silicium carbide [84], phenolic microspheres [45] and diverse flame retardants [46] are also mentioned as potential fillers or reinforcements. The chemical variety of the fillers is obvious and this often leads also to differences in particle characteristics.…”
Section: Filler Characteristics and Their Effect On Composite Propertiesmentioning
confidence: 99%
“…A large variety of materials are used as fillers in composites. Besides CaCO3 and carbon black (see Table 1) a large number of other materials like mica [63,73,95], short [96][97][98] and long glass fibers [99,100], glass beads [101][102][103][104][105][106][107][108][109][110], sepiolite [38][39][40][41][42][43][44][45][46][47][48][49], magnesium and aluminum hydroxide [111][112][113], wood flour and cellulose [30][31][32][33][34][35][36][37][115][116][117], wollastonite [102,[118][119][120], gy...…”
Section: Filler Characteristicsmentioning
confidence: 99%